Group-based nutrition education interventions are associated with an increase in nutrition knowledge and intake of carbohydrate rich foods, but not caloric intake in weight-sensitive international elite athletes - Sesbreno, E.; Tam, R.; Capling, L.; Thurecht, R.; Iwasa-Madge, K.; Dziedzic, C.; Mountjoy, M.; Brazeau, A.-S. (International Journal of Sport Nutrition and Exercise Metabolism, 2025)
Poor energy intake in athletes may result from disordered eating, misguided approaches to reduce body mass/fat and/or inadequate time, resources or knowledge to meet the increased energy needs for training or competition. Energy intake is positively associated with nutrition knowledge in athletes. Improving nutrition knowledge may offer a cost-effective approach to prevent negative performance and health outcomes associated with low energy availability (LEA) described in the Relative Energy Deficiency in Sports (REDs) syndrome model. The aim was to assess the short-term influence of 2 different 60-min group-based nutrition education interventions on sports nutrition knowledge and dietary intake in elite athletes. Twenty-five tier 4-5 level Canadian athletes across 5 sport disciplines were enrolled into a 3-week prospective single blinded randomized study. Education content was similar between both groups to increase general- and sport nutrition knowledge with only 1 group assigned 5-10mins to review a list of athletes` reported symptoms of REDs. Participants were assessed using anthropometry, restrained eating behaviour via three-factor eating questionnaire-R18, Platform to Evaluate Athlete Knowledge of Sports Nutrition Questionnaire, Athlete Food Choice Questionnaire, Eating Disorder Examination Questionnaire 6.0, Low energy availability (male or female) questionnaire, food intake record over 5 consecutive days of training and the Athlete Diet Index questionnaire before and after the intervention. At baseline, 76% under-consumed carbohydrates (4-6g/kg/d) for moderate exercise with 32% screening positive for LEA. The interventions were associated with (1) an increase in nutrition knowledge and the intake of carbohydrate rich foods (p<0.05); (2) a decrease in disorder/disordered eating symptoms and usual eating practices and weight control determinants of food choice (p<0.05); but (3) without a change in daily relative energy and carbohydrate intake (±~400kcal/d) (p>0.05). Both interventions performed similarly (p>0.05). Given the health and performance risks associated with LEA, it is important to explore different educational interventions aimed at optimizing energy and carbohydrate intake to enhance health and performance.